Identity Politics and the Muslim Voter Resistance Movement: Joko Widodo's Defeat in West Nusa Tenggara in the 2019 Presidential Election - Al-Qausyary, Zaenuddin Salim; Mar’iyah, Chusnul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This article examines the defeat of Joko Widodo in the 2019 Presidential Election in West Nusa Tenggara (NTB) by focusing on identity politics and the resistance movement among Muslim voters. The defeat was not merely the result of formal electoral factors, but was strongly influenced by local socio religious dynamics that intensified prior to the election. This study employs a qualitative approach using a case study method. Data were collected through in depth interviews with religious leaders, political volunteers, and community members, as well as document analysis and media coverage. The findings indicate that the mobilization of religious identity played a crucial role in shaping political resistance against Joko Widodo. Narratives of ulama criminalization, post-212 movement sentiments, and dissatisfaction with local political representation significantly reinforced voter opposition. This resistance movement was consolidated through networks of religious actors and volunteers who effectively produced and disseminated oppositional narratives at the local level. The study highlights that identity politics in the 2019 presidential election in NTB functioned as a powerful instrument of political mobilization capable of shifting voter preferences and influencing electoral outcomes.